Do they still matter? – Impact of Fossil Fuels on Electricity Prices in the Light of Increased Renewable Generation - Johannes Lips (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
During the last years, the German energy sector and especially its electricity market was affected by a major energy transition, the so called "Energiewende". This transition led to an increase of electricity production from renewable sources and thereby affected the whole electricity market. Therefore, it provides lessons for countries, which are only beginning a similar transition away from fossil fuels to renewable energy sources. The aim of this analysis is to assess if there still exists a relationship between fossil fuel and electricity prices. Due to possible structural breaks in the time series a minimum Lagrange Multiplier (LM) stationarity test is applied, which endogenously determines possible structural breaks. Subsequently a bootstrap approach is used to estimate con- fidence intervals (C.I.s) for the test statistic and the possible break dates. Furthermore, the stability of the cointegration vector is assessed with the test by Hansen and Jo- hansen (1999). The results indicate that the cointegration relationship is not stable over time. To incorporate these findings, the cointegration analysis is based on Johansen et al. (2000), which allows structural breaks in the deterministic part of the cointegra- tion relation. These results supports the assumption that the energy transition affected the relationship between fossil fuels and electricity prices, although there still exists a relatively strong cointegration relation between fossil fuel and electricity prices in the long run.
Keywords: C58; Q40; Q41; 330